The Impact of Social Media on the Restaurant Industry: A Bibliometric Analysis Study - MOUSTAFA, HAGAR HOSAMELDIN MOUSTAFA HAMIDO (İstanbul Kültür Üniversitesi, 2025)
This study investigates the impact of social media on the restaurant industry, focusing on customer engagement, brand perception, customer loyalty, and consumer behavior. Given the increasing role of digital platforms in shaping consumer choices, this research aims to better understand how social media contributes to restaurant success. A bibliometric study of papers indexed in Web of Science and Scopus from 2010 to 2025 is conducted using the R package Bibliometric as part of a mixed-method approach. There were 148 documents in Scopus and 148 documents on the Web of Science. This method identifies the Annual Scientific Production, Most Cited Authors, Most Cited Works, Most Relevant Sources, Most Cited Countries, and Co-occurrence Network related to social media and restaurant marketing. The findings reveal significant academic interest in the intersection of social media and hospitality, highlighting the dominant themes and trends in literature. This analysis provides valuable insights for researchers and practitioners by identifying key focus areas and revealing how social media influences customer behavior and restaurant performance. Additionally, the study suggests a conceptual research model that shows how social media presence affects restaurant results. The methodology specifically ties social media activity to menu preferences, customer interaction, and brand perception, all of which influence sales growth, customer loyalty, and overall business performance.
Keywords: Social Media; Restaurants; Bibliometric Analysis; Customer Engagement